Clinical and epidemiological profile of Kawasaki disease: Hospital Pediátrico Dr. Agustín Zubillaga (Boletin Médico de Postgrado, 2020)
A descriptive cross-sectional retrospective investigation was carried out to evaluate the clinical and epidemiological profile of Kawasaki disease (KD) in 95 children discharged from the Pediatric Hospital Dr. Agustín Zubillaga during the period 2014-2017. Mean age of children was 3.9 ± 3.3 years and 69.5% were male. Time of symptom onset was less than ten days in 68.4% patients. Predominant clinical manifestations were fever (100%), edema and/or desquamation of palms and soles (85.3%), alteration of the oral mucosa (65.3%), conjunctival injection (59%) and polymorphic erythema (55.8%). Treatment received included aspirin (100%) and immunoglobulin (96.8%). Response to treatment was satisfactory in 95.8% of cases. Laboratory findings showed elevated CRP (51.6%), thrombocytosis (97.9%) and normal hemoglobin in 62.1% patients. 41% had an abnormal echocardiogram and 97.9% showed a normal abdominal ultrasound. The diagnosis of CHD admission was incomplete in 53.7% of cases and the diagnosis of EK was complete in 51.6%. Results of this study show recent epidemiological data about Kawasaki disease in our healthcare institution.
Keywords: mucocutaneous lymph node syndrome; child; fever; edema; erythema